2022
DOI: 10.3389/fnut.2022.915681
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Disruption by Naturally Occurring Mycotoxins in Circulation: A Focus on Vascular and Bone Homeostasis Dysfunction

Abstract: Naturally occurring food/feed contaminants have become a significant global issue due to animal and human health implications. Despite risk assessments and legislation setpoints on the mycotoxins' levels, exposure to lower amounts occurs, and it might affect cell homeostasis. However, the inflammatory consequences of this possible everyday exposure to toxins on the vascular microenvironment and arterial dysfunction are unexplored in detail. Circulation is the most accessible path for food-borne toxins, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 147 publications
1
14
0
Order By: Relevance
“…The use of an immunomodulator based on recombinant α-and g-interferons (experimental Group 4) gave the best result. The increase in the bactericidal activity of the blood was caused by the immune system stimulation, based on an increase in the formation of cytokines and blocking of lymphocyte receptors, which is confirmed by the results of studies by Malvandi et al (2022).…”
Section: Immunoglobulins and Their Correction In Cows With Mycotoxico...supporting
confidence: 63%
“…The use of an immunomodulator based on recombinant α-and g-interferons (experimental Group 4) gave the best result. The increase in the bactericidal activity of the blood was caused by the immune system stimulation, based on an increase in the formation of cytokines and blocking of lymphocyte receptors, which is confirmed by the results of studies by Malvandi et al (2022).…”
Section: Immunoglobulins and Their Correction In Cows With Mycotoxico...supporting
confidence: 63%
“…AFB1 has been shown to bind to the VDR, a protein that acts as the receptor for vitamin D [ 22 ]. This competitive binding effectively blocks vitamin D from interacting with the VDR, hindering its ability to maintain calcium and phosphorus homeostasis [ 23 ]. Chronic exposure to AFB1 can also lead to a decrease in the expression of VDR itself.…”
Section: Discussionmentioning
confidence: 99%
“…The liver damage, production of reactive oxygen species and interference with cellular processes caused by aflatoxicosis might intensify bone health issues in modern broilers. Recent human and animal studies have revealed new insights into the bone disorders caused by aflatoxicosis, where AFB1 interferes with the expression and function of the vitamin D receptor (VDR), affecting the metabolism of vitamin D2 and D3 into 25-hydroxycholecalciferol (25-OH) and 1,25-dihydroxycholecalciferol (1,25-OHD), resulting in decreased bone quality [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…51,52 It was found that mycotoxins can disrupt lipid metabolism by affecting the expression of key genes and enzymes involved in lipid synthesis, oxidation, and transport. 53 Additionally, mycotoxins can induce inammation and oxidative stress, further contributing to lipid dysregulation. 54 Herein, we quantitatively determined 44 FAs in the feces and plasma of DON exposure mice by the validated GC-MS/MS method.…”
Section: Deoxynivalenol Induced Kidney Injury Associated Fa Metabolis...mentioning
confidence: 99%